2018
DOI: 10.1590/s0102-865020180050000004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of red propolis on hamster cheek pouch angiogenesis in a new sponge implant model

Abstract: Effect of red propolis on hamster cheek pouch angiogenesis in a new sponge implant model 1 Abstract Purpose: To evaluate the effects of red propolis on cheek pouch angiogenesis in a hamster new model sponge implant. Methods: Forty eight animals divided into eight groups. (Groups I-IV), the animals were treated for 15 days before and 10 days after sponge implantation. (Groups V-VIII), the animals were treated for 10 days after sponge implantation (GI and GV: red propolis 100 mg/kg, GII and GVI: celecoxib 20 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…In earlier experiments on animal models conducted by our team, red propolis inhibited inflammatory and neoplastic angiogenesis associated with a reduction in inflammatory cells (e.g., mastocytes and macrophages) suggestive of immunomodulatory action 26 , 27 .…”
Section: Discussionmentioning
confidence: 70%
“…In earlier experiments on animal models conducted by our team, red propolis inhibited inflammatory and neoplastic angiogenesis associated with a reduction in inflammatory cells (e.g., mastocytes and macrophages) suggestive of immunomodulatory action 26 , 27 .…”
Section: Discussionmentioning
confidence: 70%
“…The findings on propolis' actions regarding neovascularization and angiogenesis have shown contradicting results. In some studies, propolis positively affects angiogenesis (Abdel-Wahed et al, 2013;Nindra et al, 2021;Staniczek et al, 2021;Sungkar et al, 2021), and in other studies it negatively affects angiogenesis (Chikaraishi et al, 2010;Lima et al, 2014;Melo et al, 2018). Sungkar et al (2021) reported that EEP from Mount Lawu, Indonesia has angiogenic effects or promotes angiogenesis through decreased malondialdehyde blood levels and IL-6 blood levels, and an increase in vascular endothelial growth factor (VEGF) blood levels.…”
Section: Stimulation Of Angiogenesis and Neovascularizationmentioning
confidence: 99%
“…The findings on propolis' actions regarding neovascularization and angiogenesis have shown contradicting results. In some studies, propolis positively affects angiogenesis (Abdel‐Wahed et al, 2013; Nindra et al, 2021; Staniczek et al, 2021; Sungkar et al, 2021), and in other studies it negatively affects angiogenesis (Chikaraishi et al, 2010; Lima et al, 2014; Melo et al, 2018).…”
Section: Wound Healing Effects Of Propolismentioning
confidence: 99%
See 1 more Smart Citation
“…Complement, lymphocyte and macrophage activation has been observed in many studies, suggesting they are part of the mechanism by which propolis induces apoptosis in tumor cells. ( 11 13 ) In this way, we therefore included an experiment with 33 days of treatment with propolis prior to inoculation (experiment 2).…”
Section: Introductionmentioning
confidence: 99%